A Novel Route to 6-Substituted Piperidin-3-ols via Domino Cyclization of 2-Hydroxy-6-phosphinyl-5-hexenyl Tosylates with Primary Amines: Synthesis of (±)-Pseudoconhydrine and (±)-epi-Pseudoconhydrine - Scherner, Cathrin; Ergüden, Jens-Kerim; Adiwidjaja, Gunadi; Schaumann, Ernst (Synthesis, 2014)
2-Hydroxy-6-phosphinyl-5-hexenyl tosylates, oxirane ring-opening products derived from glycidyl tosylates and phosphinyl-substituted allyl anions, undergo domino SN2–Michael reactions with primary amines to give 6-phosphinylmethylpiperidin-3-ols. The phosphinyl unit can be used in Horner olefination reactions. This approach is applied to the synthesis of racemic pseudoconhydrine and its epimer.
Keywords: phosphine oxides; domino reactions; cyclization; piperidines; Horner olefination